Learning and literacy objects: a proposal to use playful resources for children with learning difficulties - Fiscarelli, Silvio Henrique [UNESP]; Morgado, Camila Lourenco [UNESP]; Uehara, Flavia Maria (Centro Univ La Salle-rj, 2017)
This paper presents the partial results of in progress research that aims to investigate the use of Learning Objects (LO) as resources to support students with difficulties in the literacy process in the initial years of Elementary Education. The goals of research is verify if the use of this technological resource, outside of school environment, can help the students to surpass difficulties in the literacy process diagnosed in the classroom. The research explore some characteristics of the technological resources, in this specific case, the characteristics of Learning Objects, that allow presenting curricular contents in a playful way and alternative practices for learning. Although the research is still in progress, the outcomes obtained at the moment indicate that students who participated in activities with LO have surpass some learning difficulties and obtained a better classification in the diagnostic evaluations.
Keywords: Learning Objects; Literacy; Learning Disabilities